Ag-based transparent composite electrode and preparation method thereof, Ag-based transparent thin film heater with high thermal stability

By introducing Ga-Ag seed layer into the Ag-based transparent composite electrode, the migration and agglomeration of Ag atoms is suppressed, and the shortcomings of the transparent heater in terms of cost, transparency and thermal output stability are solved, and efficient and stable thermal output is achieved.

CN118764990BActive Publication Date: 2025-02-28SHANDONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411015677.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-02-28
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

Existing transparent heaters have shortcomings in cost, transparency and thermal output stability, and Ag-based transparent composite electrodes are prone to atom migration and agglomeration during growth, resulting in optical and electrical losses.

Method used

The Ga-Ag seed layer is used as the transition layer for the Ag layer growth, and the SiOx film, the Ga-Ag seed layer, the Ag film and the oxide layer are deposited by magnetron sputtering method to form an Ag-based transparent composite electrode. Ga in the Ga-Ag seed layer can penetrate into the Ag grain boundary, inhibit Ag atom migration and agglomeration, and improve the continuity and conductivity of the film.

Benefits of technology

The high optical transparency, conductivity and thermal stability of the Ag-based transparent composite electrode are achieved, which reduces optical and electrical losses, improves thermal output efficiency, and solves the instability problem of traditional Ag-based transparent composite electrodes in thermal environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention discloses an Ag-based transparent composite electrode and a preparation method thereof, and an Ag-based transparent thin film heater with high thermal stability, belonging to the technical field of flexible transparent heaters. The Ag-based transparent composite electrode comprises a SiO2 arranged from bottom to top. x layer, Ga‑Ag seed layer, Ag layer and oxide layer. Among them, the Ga‑Ag seed layer is a Ga‑Ag alloy film with Ga:Ag=2.8:1 deposited by magnetron sputtering. The present invention cleverly coats the liquid metal Ga on the surface of the Ag sheet, fixes it on the surface of the target material at the Ag target position, and obtains a Ga‑Ag alloy target. The Ga‑Ag seed layer obtained by sputtering reduces the threshold thickness of the Ag film to reach continuity, reduces photon and electron losses, and improves the optical transmittance and conductivity of the heater; at the same time, Ga also effectively inhibits the migration and agglomeration of Ag atoms, and improves the thermal stability of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flexible transparent heaters, and in particular relates to an Ag-based transparent composite electrode and a preparation method thereof, and an Ag-based transparent thin film heater with high thermal stability. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] A transparent heater is an optically transparent heating device that includes a conductive layer. When an external bias is connected, Joule heat is generated when current flows through the conductive layer. This part of the heat of the transparent heater can be fully utilized in different scenarios, such as construction, agriculture, and medical fields. At present, the applications of transparent heaters in society mainly include: defogging and deicing glass for vehicles, smart energy-saving windows for buildings, wearable thermotherapy sheets in the medical field, smart insulation film layers for greenhouses and sheds, etc. These applications require transparent heaters to have good optical transparency, thermal stability and thermal output efficiency in terms of performance, and require low-cost materials and simple process flows in terms of economy. At the same time, some special fields also require devices to have certain mechanical flexibility. At present, there are still many problems with the more mainstream preparation technology for transparent heaters, such as the mechanical brittleness of transparent conductive oxides, the complex preparation process of carbon-based nanomaterials, the incompatible mechanical properties and conductivity of ionic liquid gels, and the chemical corrosion and electrical short circuit of metal nanowire networks.

[0004] Ag thin films deposited and grown by magnetron sputtering have been widely studied in the field of transparent composite electrodes due to their inherent ductility and high conductivity. However, Ag has poor wettability on oxide substrates, and the traditional three-dimensional island growth pattern forms a porous surface, resulting in large optical and electrical losses. At the same time, Ag atoms will have obvious migration and agglomeration behaviors in thermal environments. These problems make it difficult to integrate Ag-based transparent composite electrodes into transparent heating devices. How to induce Ag to grow in two-dimensional lateral direction and reduce the continuous thickness threshold of the film is the key to improving the transparency and constant-pressure heat output capacity of Ag thin films. At the same time, it is not easy to overcome the thermal migration behavior of Ag atoms without generating large electrical losses. Summary of the invention

[0005] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide an Ag-based transparent composite electrode and a preparation method thereof, and an Ag-based transparent thin film heater with high thermal stability. The device obtained by the present invention can have optical transparency, conductivity, thermal stability and thermal output efficiency, and solves the problems of high cost, low transparency and unstable thermal output of transparent heaters.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] The first aspect of the present invention provides an Ag-based transparent composite electrode, comprising SiO x Thin film layer, Ga-Ag seed layer, Ag thin film layer and oxide layer;

[0008] The atomic content of the Ga-Ag seed layer is Ga:Ag=0.1-14:1.

[0009] The present invention provides an Ag-based transparent composite electrode. The present invention ingeniously utilizes the mechanism that liquid gallium can corrode Ag metal and introduces a Ga-Ag seed layer as a transition layer for the growth of the Ag layer. The Ga-Ag seed layer can effectively solve the problem of poor wettability of Ag to an oxide substrate. Ga in the Ga-Ag seed layer can penetrate into the Ag grain boundary, which is conducive to inhibiting the atomic migration and agglomeration of Ag during the growth process, thereby obtaining an ultra-thin and continuous Ag film; it is conducive to inhibiting the surface plasma resonance effect caused by discontinuous clusters, and can significantly reduce the optical loss of the Ag-based transparent composite electrode. At the same time, the continuous film layer inhibits the electron scattering phenomenon caused by the island morphology during the current transmission process, so that the electrode obtains a higher conductivity. This is conducive to the Ag-based transparent thin film heater working under a constant voltage DC power supply to achieve higher heat output. The Ag film grown on the Ga-Ag seed layer does not have obvious holes, has low surface roughness, and has fine, dense and uniform particles; at the same time, the presence of a large number of edge dislocations hinders the migration of Ag atoms and Ag particles. This makes an important contribution to improving the heat generation uniformity and thermal stability of Ag-based transparent thin film heaters during operation.

[0010] The second aspect of the present invention provides a method for preparing the Ag-based transparent composite electrode, comprising the following steps:

[0011] SiO was deposited on the substrate by magnetron sputtering. x Thin film, substrate / SiO x ;

[0012] The substrate / SiO x The substrate was used as the substrate, and a Ga-Ag alloy target was used to deposit and grow a Ga-Ag seed layer on it by magnetron sputtering to obtain a substrate / SiO x / Ga-Ag;

[0013] The substrate / SiO x / Ga-Ag is used as the substrate, and Ag thin film is deposited and grown on it using Ag target by magnetron sputtering to obtain substrate / SiO x / Ga-Ag / Ag;

[0014] The substrate / SiO x / Ga-Ag / Ag is used as a substrate, and a magnetron sputtering method is used to deposit and grow an oxide film as a protective layer thereon to obtain an Ag-based transparent composite electrode.

[0015] The third aspect of the present invention provides an application of the Ag-based transparent composite electrode in a heater.

[0016] A fourth aspect of the present invention provides an Ag-based transparent thin film heater with high thermal stability, comprising the Ag-based transparent composite electrode and a power source; the Ag-based transparent composite electrode is connected to the power source to form a closed loop.

[0017] The beneficial effects of the present invention are:

[0018] The present invention ingeniously utilizes the mechanism that liquid gallium can corrode Ag metal, and further prepares a Ga-Ag alloy target by forming a Ga-Ag alloy sheet, thereby introducing a Ga-Ag seed layer as a transition layer for the growth of the Ag layer. The Ga-Ag seed layer can effectively solve the problem of poor wettability of Ag to the oxide substrate.

[0019] Ga in the Ga-Ag seed layer can penetrate into the Ag grain boundary, which is beneficial to suppress the atomic migration and agglomeration of Ag during the growth process, thereby obtaining an ultra-thin and continuous Ag film. It is beneficial to suppress the surface plasma resonance effect caused by discontinuous clusters. The low-thickness film layer also reduces the transmission distance of photons in the Ag film, which can significantly reduce the optical loss of the Ag-based transparent composite electrode. At the same time, the continuous film layer suppresses the electron scattering phenomenon caused by the island morphology during current transmission, so that the electrode obtains a higher conductivity, which is beneficial to the Ag-based transparent film heater working under a constant voltage DC power supply to achieve higher heat output.

[0020] The Ag film grown on the Ga-Ag seed layer has no obvious holes, low surface roughness, fine and dense particles; at the same time, the presence of a large number of edge dislocations hinders the migration of Ag atoms and Ag particles. This has an important contribution to the improvement of the heat generation uniformity and thermal stability of the Ag-based transparent thin film heater during operation.

[0021] The present invention adopts low-content, high-purity Ga doping to prepare Ga-Ag alloy target, and obtains an extremely thin seed layer with a thickness of less than 2nm under low sputtering power. This realizes the minimization of the introduction of heterogeneous atoms in the Ag-based transparent composite electrode, while improving the performance of the Ag film, and avoiding the deterioration of optical and electrical properties caused by Ga atoms in the electrode to the greatest extent.

[0022] The present invention adopts a new method of metal mutual dissolution, so that the Ga metal that is easily fusible at room temperature is successfully introduced into the Ag-based transparent composite electrode as a Ga-Ag seed layer, which provides a new material selection and preparation method for the introduction of the traditional metal wetting layer. At the same time, the implementation of the Ag-based flexible transparent thin film heater preparation method has low requirements on experimental equipment and simple process operation; the electrode is compatible with a wide range of substrates and is easy to be applied in multiple fields; the raw material stoichiometric ratio and process parameters can be accurately controlled, and the product performance is stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0024] Figure 1 A schematic diagram of the structure of a Ag-based transparent composite electrode prepared in an embodiment of the present invention;

[0025] Figure 2 A schematic diagram of the structure of an Ag-based flexible transparent thin film heater prepared in an embodiment of the present invention;

[0026] Figure 3 The AFM morphology images of the Ag thin film layer in the Ag-based flexible transparent thin film heater prepared in Example 1 and Comparative Example 1 of the present invention; wherein A is the AFM morphology image of the Ag thin film layer without the Ga-Ag seed layer prepared in Comparative Example 1, and B is the AFM morphology image of the Ag thin film layer with the Ga-Ag seed layer prepared in Example 1;

[0027] Figure 4 The optical transmittance and resistivity of the Ag-based flexible transparent thin film heaters prepared in the embodiments of the present invention and the comparative examples under the condition of wetting with Ga-Ag seed layers of different concentrations;

[0028] Figure 5 The heat output performance curves of the Ag-based flexible transparent thin film heaters prepared in Example 1 and Comparative Example 1 of the present invention under variable pressure; wherein SgaAZ represents the Ag-based flexible transparent thin film heater prepared in Example 1, and SAZ represents the Ag-based flexible transparent thin film heater prepared in Comparative Example 1;

[0029] Figure 6 The temperature variation curve of the Ag-based flexible transparent thin film heater prepared in Example 1 of the present invention under repeated bending;

[0030] Figure 7The thermal stability performance curves of the Ag-based flexible transparent thin film heaters prepared in Example 1 and Comparative Example 1 of the present invention under cyclic on-off voltage; wherein SgaAZ represents the Ag-based flexible transparent thin film heater prepared in Example 1, and SAZ represents the Ag-based flexible transparent thin film heater prepared in Comparative Example 1.

[0031] Figure 1 and Figure 2 The reference numerals in the figure are: 1-Ag-based transparent composite electrode, 101-substrate, 102-SiO x Thin film layer, 103-Ga-Ag seed layer, 104-Ag thin film layer, 105-oxide layer (also the zinc oxide layer in Example 1), 2-conductive copper sheet, 3-external bias, 4-source meter. DETAILED DESCRIPTION

[0032] The "atomic content" mentioned in the present invention refers to the number of atoms, and "the atomic content in the Ga-Ag seed layer 103 is Ga:Ag=0.1~14:1" means that in the Ga-Ag seed layer, the atomic number ratio of Ga to Ag is 0.1~14:1.

[0033] In view of the problems of high cost, low transparency, unstable heat output and the like of current transparent heaters, the present invention provides an Ag-based transparent composite electrode and a preparation method thereof, and an Ag-based transparent thin film heater with high thermal stability.

[0034] The Ag-based transparent composite electrode and the Ag-based transparent thin film heater with high thermal stability provided by the present invention have simple preparation processes, require a wide range of materials, use less process amounts, have low preparation costs, and can precisely control the stoichiometric ratio of raw materials and instrument processing parameters, thereby ensuring the stability of product performance. The resulting device can have both optical transparency, electrical conductivity, thermal stability, and thermal output efficiency. At the same time, the Ag-based transparent composite electrode and the Ag-based transparent thin film heater can use hard substrates such as glass, and can also be compatible with organic polymer substrates such as PET and PI, and have a wide range of applications.

[0035] A typical embodiment of the present invention provides an Ag-based transparent composite electrode, such as Figure 1 As shown, it includes sequentially arranging SiO x Thin film layer 102, Ga-Ag seed layer 103, Ag thin film layer 104 and oxide layer 105;

[0036] The atomic content of the Ga—Ag seed layer 103 is Ga:Ag=0.1-14:1.

[0037] The present invention provides an Ag-based transparent composite electrode with an oxide-metal-oxide (OMO) structure, which is an OMO-structured transparent composite electrode containing an intermediate conductive metal layer encapsulated by a bottom oxide layer and a top oxide layer. How to achieve the growth of an ultra-thin continuous film on the bottom oxide surface and inhibit the migration of Ag atoms in the intermediate conductive metal layer in a high-temperature working environment is the key to improving the photoelectric performance and thermal stability of the Ag-based transparent thin film heater.

[0038] The present invention is cleverly designed to x A Ga-Ag seed layer 103 is introduced between the thin film layer 102 and the Ag thin film layer 104. The Ga-Ag seed layer 103 serves as a transition layer for the growth of the Ag thin film layer 104. The Ga-Ag seed layer 103 can effectively solve the problem of poor wettability of Ag on the oxide substrate. The Ga-Ag seed layer 103 can reduce the threshold thickness of the Ag thin film to reach continuity, reduce photon and electron losses, and improve the optical transmittance and conductivity of the heater; at the same time, Ga also effectively inhibits the migration and agglomeration of Ag atoms, improving the thermal stability of the device.

[0039] Ga in the Ga-Ag seed layer 103 can penetrate into the Ag grain boundary, which is conducive to suppressing the atomic migration and agglomeration of Ag during the growth process, thereby obtaining an ultra-thin and continuous Ag film. This is conducive to suppressing the surface plasma resonance effect caused by discontinuous clusters, and the low-thickness film layer also reduces the transmission distance of photons in the Ag film, which can significantly reduce the optical loss of the Ag-based transparent composite electrode. At the same time, the continuous film layer suppresses the electron scattering phenomenon caused by the island morphology during the current transmission process, so that the electrode obtains a higher conductivity, which is conducive to the Ag-based transparent film heater working under a constant voltage DC power supply to achieve a higher heat output.

[0040] In some examples of this embodiment, the atomic content of the Ga-Ag seed layer 103 is preferably Ga:Ag = 0.9~13.8:1, specifically 0.9:1, 1:1, 2:1, 2.8:1, 5:1, 6:1, 8:1, 10:1, 12:1, 13:1, 13.8:1, etc., preferably 2.8:1.

[0041] In some examples of this embodiment, the Ag-based transparent composite electrode is compatible with both hard substrates and flexible substrates.

[0042] When the Ag-based transparent composite electrode is integrated onto a hard substrate, it can be applied to anti-fogging and defrosting of vehicles and exterior display screens.

[0043] When Ag-based transparent composite electrodes are integrated onto flexible substrates, they can be applied to wearable thermotherapy sheets, smart thermal insulation film layers for greenhouses or sheds, and heating components for foldable electronic devices.

[0044] In some examples of this embodiment, the SiO x The thickness of the thin film layer 102 is 8-12 nm, specifically 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, etc., preferably 10 nm.

[0045] In some examples of this embodiment, the thickness of the Ga-Ag seed layer 103 is less than 2nm and not 0, specifically 0.1nm, 0.3nm, 0.5nm, 0.7nm, 0.9nm, 1nm, 1.2nm, 1.4nm, 1.5nm, 1.6nm, 1.8nm, 1.9nm, etc., preferably 1.5nm.

[0046] In some examples of this implementation, the thickness of the Ag thin film layer 104 is 7-8 nm, specifically 7 nm, 7.1 nm, 7.2 nm, 7.3 nm, 7.4 nm, 7.5 nm, 7.6 nm, 7.7 nm, 7.8 nm, 7.9 nm, 8 nm, etc., preferably 7.5 nm. The thin film layer reduces the transmission distance of photons in the Ag film, which can significantly reduce the optical loss of the Ag-based transparent composite electrode.

[0047] The Ag film grown on the Ga-Ag seed layer 103 has no obvious holes, low surface roughness, fine, dense and uniform particles; at the same time, the presence of a large number of edge dislocations hinders the migration of Ag atoms and Ag particles. This has an important contribution to improving the heat generation uniformity and thermal stability of the Ag-based transparent thin film heater during operation.

[0048] In some examples of this embodiment, the oxide layer 105 is 30-40 nm, specifically 30 nm, 31 nm, 32 nm, 33 nm, 34 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm, 40 nm, etc., preferably 35 nm.

[0049] In some examples of this embodiment, the oxide is zinc oxide.

[0050] In some examples of this embodiment, SiO x The thickness of the thin film layer 102 is 10 nm; the thickness of the Ga—Ag seed layer 103 is 1.5 nm; the thickness of the Ag thin film layer 104 is 7.5 nm; and the thickness of the zinc oxide layer 105 is 35 nm.

[0051] Another typical embodiment of the present invention provides a method for preparing the Ag-based transparent composite electrode, comprising the following steps:

[0052] SiO was deposited on the substrate by magnetron sputtering. x Thin film, substrate / SiO x;

[0053] The substrate / SiO x The substrate was used as the substrate, and a Ga-Ag alloy target was used to deposit and grow a Ga-Ag seed layer on it by magnetron sputtering to obtain a substrate / SiO x / Ga-Ag;

[0054] The substrate / SiO x / Ga-Ag is used as the substrate, and Ag thin film is deposited and grown on it using Ag target by magnetron sputtering to obtain substrate / SiO x / Ga-Ag / Ag;

[0055] The substrate / SiO x / Ga-Ag / Ag is used as a substrate, and a magnetron sputtering method is used to deposit and grow an oxide film as a protective layer thereon to obtain an Ag-based transparent composite electrode.

[0056] The present invention adopts a new method of metal mutual dissolution, so that the Ga metal that is easily fusible at room temperature is successfully introduced into the Ag-based transparent composite electrode as a Ga-Ag seed layer, which provides a new material selection and preparation method for the introduction of the traditional metal wetting layer. At the same time, the implementation of the Ag-based transparent composite electrode preparation method has low requirements for experimental equipment and simple process operation; the electrode is compatible with a wide range of substrates and is easy to be applied in multiple fields; the raw material stoichiometric ratio and process parameters can be accurately controlled, and the product performance is stable.

[0057] In some embodiments of this embodiment, the substrate is a hard transparent substrate or a flexible transparent substrate. The hard transparent substrate includes but is not limited to glass, and the flexible transparent substrate includes but is not limited to PET and PI. Among them, the substrate is preferably a polyimide (PI) film. For example, a PI film with a size of 30 mm*40 mm and a thickness of 0.05 mm can be used as the substrate.

[0058] In some examples of this embodiment, the oxide is deposited on the substrate by magnetron sputtering under a radio frequency power supply, and the metal is deposited on the substrate by magnetron sputtering under a direct current power supply.

[0059] The purity of all oxide target materials used in the radio frequency power supply is preferably ≥99.99%, and the purity of all pure metal target materials used in the direct current power supply is preferably ≥99.9999%.

[0060] In some examples of this implementation mode, the RF power sputtering power of all oxide targets is 80W, the DC power sputtering power of the Ga-Ag alloy target is 5W, and the DC power sputtering power of the Ag target is 10W.

[0061] In some examples of this implementation mode, the method for preparing the Ga-Ag alloy target comprises the following steps:

[0062] The preparation method of the Ga-Ag alloy target comprises the following steps:

[0063] Drop liquid Ga onto the surface of the Ag sheet, then heat the Ag sheet to 30-60°C, evenly apply the liquid Ga to completely cover the surface of the Ag sheet, and keep the temperature constant until Ga corrodes the Ag sheet;

[0064] After the heat preservation is completed, the Ag thin sheet with Ga on the surface is frozen to obtain a Ga-Ag alloy sheet;

[0065] According to the requirement of atomic content in the Ga-Ag seed layer, a Ga-Ag alloy sheet is fixed on the surface of the target material at the Ag target position to obtain a Ga-Ag alloy target.

[0066] The present invention adopts a coating method to prepare a Ga-Ag alloy target. The so-called coating method for preparing a Ga-Ag alloy target refers to coating a certain amount of liquid Ga metal on the surface of an Ag thin slice, Ga will penetrate into the Ag grain boundary and cause certain corrosion to it, and a number of Ag thin slices dissolved with Ga are fixed on the surface of the target material at the positions of equally divided Ag targets to obtain a Ga-Ag alloy target that can achieve a co-deposition effect.

[0067] The Ga-Ag alloy target was prepared by low-content, high-purity Ga doping, and an extremely thin Ga-Ag seed layer with a thickness of less than 2nm was obtained at low sputtering power. This minimized the introduction of heterogeneous atoms in the Ag-based transparent composite electrode, while improving the performance of the Ag film and avoiding the deterioration of the optical and electrical properties caused by Ga atoms in the electrode to the greatest extent.

[0068] In some examples of this implementation mode, multiple Ga-Ag alloy sheets can be prepared, and the multiple Ga-Ag alloy sheets can be fixed on the surface of the target material at the equally divided Ag target positions to obtain a Ga-Ag alloy target. Alternatively, according to the requirements of the atomic content in the Ga-Ag seed layer, a Ga-Ag alloy sheet can be prepared and fixed on the surface of the target material at the Ag target position to obtain a Ga-Ag alloy target.

[0069] In some examples of this embodiment, when preparing the Ga-Ag alloy target, the purity of the liquid Ga is preferably 99.9999%.

[0070] In some examples of this implementation mode, 0.1-0.3 mL of liquid Ga can be dropped onto the surface of a rectangular Ag sheet with a size of 60 mm*6-8 mm and a thickness of 0.1 mm, and multiple Ga-Ag alloy sheets can be fixed on the target surface at equally divided Ag target positions to obtain a Ga-Ag alloy target.

[0071] Preferably, when preparing a Ga-Ag alloy target, the purity of the liquid Ga is 99.9999%; the amount of liquid gallium used for each Ga-Ag alloy sheet is 0.2 mL; the size of the rectangular Ag sheet is 60 mm*7 mm, and the thickness is 0.1 mm; the Ag sheet is heated to 45°C; the Ag sheet with liquid Ga applied on the surface is kept warm for 3 minutes; and the three prepared Ga-Ag alloy sheets are fixed on the target surface at the six equally divided Ag target positions.

[0072] In some embodiments of this embodiment, 0.7 to 0.8 mL of liquid Ga may be dropped into A Ga-Ag alloy sheet is prepared on the surface of a circular Ag thin sheet with a thickness of 0.1 mm, and is fixed on the surface of the target material at the Ag target position to obtain a Ga-Ag alloy target.

[0073] Wherein, the insulation time is 1 to 5 minutes, specifically 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, etc., preferably 3 minutes.

[0074] Wherein, the freezing time is greater than 2h.

[0075] In some embodiments of this embodiment, the magnetron sputtering is performed in a vacuum chamber at a temperature of 20 to 25°C, a distance between the target and the substrate of 18 to 22 cm, a sputtering angle of 90°, and a base pressure of 3.5×10 -4 Pa, argon is introduced as protective gas and ionization gas, the gas flow rate is 45-55 sccm, and finally the working gas pressure is maintained at 0.7-1.0 Pa.

[0076] Preferably, the magnetron sputtering deposition of each film layer is completed in a vacuum chamber in an ultra-high vacuum magnetron sputtering system, the temperature of the vacuum chamber is adjusted to 21°C, the distance between the target and the sample is 20 cm, the sputtering angle is 90°, and the background pressure is pumped to 3.5×10 -4 Pa, argon gas was introduced as protective gas and ionization gas, the gas flow rate was 50 sccm, and finally the working gas pressure was maintained at 0.8 Pa.

[0077] In some embodiments of this embodiment, each target material to be used is pre-sputtered before starting sputtering, using Ar + Clean the target surface.

[0078] A third typical implementation of the present invention provides an application of the Ag-based transparent composite electrode in a heater.

[0079] A fourth typical implementation of the present invention provides an Ag-based transparent thin film heater with high thermal stability, comprising the Ag-based transparent composite electrode and a power source; the Ag-based transparent composite electrode is connected to the power source to form a closed loop.

[0080] Figure 2 This is a structural diagram of the Ag-based transparent thin film heater with high thermal stability prepared by the present invention, which includes an Ag-based transparent composite electrode 1, a conductive copper sheet 2, an external bias voltage 3, and a source meter 4 (i.e., a power supply). The Ag-based transparent composite electrode 1 and the source meter 4 (i.e., the power supply) are connected through the conductive copper sheet 2 and the external bias voltage 3 to form a closed loop.

[0081] In some examples of this implementation manner, the power supply is a direct current power supply.

[0082] The Ag-based transparent film heater provided by the present invention has certain flexibility, and has an optical transmittance of more than 90%, lower surface resistance, and faster heating rate. It can maintain a relatively stable steady-state temperature during repeated bending and can work stably for more than 1000 cycles in a periodic On-Off voltage test.

[0083] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0084] The reagents used in the following examples are all conventional commercially available products and can be purchased.

[0085] Example 1

[0086] A Ag-based flexible transparent thin film heater with high thermal stability, the preparation method of which is as follows:

[0087] 1. Substrate Preparation

[0088] A 0.05 mm thick transparent polyimide film was cut into a rectangle of 30 mm*40 mm in size, and after removing the protective film, it was fixed to the surface of the sample stage with a polyimide high temperature tape.

[0089] 2. Preparation of Ga-Ag alloy target

[0090] 1) Heat a 99.9999% pure gallium block to a liquid state, use a pipette to measure 0.2 mL of liquid Ga and drop it onto the surface of a rectangular Ag sheet with a size of 60 mm*7 mm and a thickness of 0.1 mm, then heat the Ag sheet to 45°C, use a plastic rod to evenly spread the liquid Ga until it completely covers the surface of the Ag sheet, and keep it warm for 3 minutes until Ga produces moderate corrosion on the Ag sheet.

[0091] 2) After the heat preservation is completed, the Ag sheet covered with Ga on the surface is placed in a freezer and frozen for more than 2 hours to obtain a Ga-Ag alloy sheet.

[0092] 3) Repeat steps a and b to obtain three Ga-Ag alloy sheets, which are fixed on the target surface at six equally divided Ag target positions to obtain a Ga-Ag alloy target.

[0093] 3. Sputtering environment treatment

[0094] (1) Install the sample stage and target into the vacuum chamber of the ultra-high vacuum magnetron sputtering system, adjust the temperature of the vacuum chamber to 21°C, the distance between the target and the sample to 20 cm, and the sputtering angle to 90°. Pump the background pressure of the vacuum chamber to 3.5×10 -4 Pa, argon gas was introduced as protective gas and ionization gas, the gas flow rate was 50 sccm, and finally the working gas pressure was maintained at 0.8 Pa.

[0095] (2) Before the formal sputtering begins, the shielding plate is covered and the target surface is cleaned under the bombardment of the Ar ion beam: an 80W RF sputtering power is used to clean the 99.99% pure SiO x The Ag target with a purity of 99.9999% and the Ga—Ag alloy target were pre-sputtered for 10 minutes using a DC power supply with a sputtering power of 10 W.

[0096] 4. Preparation of Ag-based transparent composite electrodes

[0097] 1) The RF power supply sputters for 3 minutes at a sputtering power of 80 W, and a SiO layer with a thickness of 10 nm is deposited on the substrate. x Thin film, substrate / SiO x .

[0098] 2) Using the substrate / SiO obtained in step (1) x The substrate was sputtered for 4 s at a sputtering power of 5 W using a DC power supply to deposit and grow a Ga-Ag seed layer with a thickness of 1.5 nm to obtain a substrate / SiO x / Ga-Ag, and the atomic content in the Ga-Ag seed layer is Ga:Ag=2.8:1.

[0099] 3) Using a DC power supply with a sputtering power of 10 W, the substrate / SiO x / Ga-Ag was sputtered for 63s to obtain a 7.5nm thick Ag film, forming a substrate / SiO x / Ga-Ag / Ag.

[0100] 4) Using the substrate / SiO obtained in step (3) x / Ga-Ag / Ag was used as the substrate, and a 35nm thick ZnO film was grown on it for 3min 45s using a RF power supply with a sputtering power of 80W to serve as the electrode protection layer. x / Ga-Ag / Ag / ZnO, that is, preparation of Ag-based transparent composite electrode.

[0101] 5. Preparation of Ag-based flexible transparent film heater

[0102] On substrate / SiO x An external bias is applied to both ends of the Ag-based transparent composite electrode configured with Ga-Ag / Ag / ZnO to form a closed loop, thereby obtaining an Ag-based flexible transparent thin film heater.

[0103] The Ag-based transparent composite electrodes in the devices prepared in Example 1 and Comparative Example 1 were scanned using an atomic force microscope. The results are as follows: Figure 3 As shown, compared with the traditional Ag film (i.e., the Ag film in the Ag-based transparent composite electrode obtained in Comparative Example 1), the Ag film grown on the Ga-Ag seed layer has a more continuous and uniform morphology and a lower surface roughness. The minimum Ag thickness for forming a continuous layer is 7.5nm, and its surface roughness is 1.01nm.

[0104] The Ag-based flexible transparent thin film heater prepared in this embodiment was optically and electrically analyzed using a UV-visible spectrophotometer and a four-probe surface low impedance analyzer. The results are as follows: Figure 4 As shown in the figure, the device has a high transmittance in the visible light region, up to 94%, and has a 9.1Ω·sq -1 Surface resistance.

[0105] like Figure 5 As shown, under the action of increasing external bias voltage, compared with the traditional Ag-based flexible transparent thin film heater (i.e., the heater obtained in Comparative Example 1), the Ag-based flexible transparent thin film heater prepared in this embodiment can generate higher heat output and has an extremely fast thermal response speed of up to 7.4°C / s. Figure 6 It shows that the Ag-based flexible transparent film heater still has a relatively stable heat output in the stretched and contracted state after 50,000 repeated bends, indicating that the electrode has good compatibility with the flexible substrate. Figure 7 As shown, the Ag-based flexible transparent thin film heater prepared in this embodiment can work normally for about 1100 cycles at an initial heating temperature of 525K, and the temperature decrease is less than 9.6%, and the thermal stability is significantly better than that of the traditional Ag-based flexible transparent thin film heater.

[0106] Example 2

[0107] A Ag-based flexible transparent thin film heater with high thermal stability is prepared according to the method of Example 1, except that when preparing a Ga-Ag alloy target, the Ga-Ag alloy sheet with a thickness of 0.1 mm in Example 1 is cut to a size of 60 mm*2 mm, and two Ga-Ag alloy sheets are fixed on the surface of the target material at the positions of the quartered Ag target to obtain a Ga-Ag alloy target, and the atomic content of the subsequently prepared Ga-Ag seed layer is Ga:Ag=0.9:1.

[0108] The Ag film in the Ag-based flexible transparent thin film heater obtained in this embodiment is relatively continuous and has low surface roughness.

[0109] The Ag-based flexible transparent film heater prepared in this embodiment has a high transmittance in the visible light region, which can reach up to 88%, and has a thermal conductivity of 9.3Ω·sq -1 Surface resistance ( Figure 4 ).

[0110] The Ag-based flexible transparent thin film heater obtained in this embodiment was subjected to the same thermal performance test method as in Example 1. The results show that the device can generate a higher heat output and has a faster thermal response speed; the device still has a relatively stable heat output after repeated bending, indicating that the electrode has good compatibility with the flexible substrate; the device can work normally for a long time at an initial heating temperature of 525K, and the temperature drop is small, and the thermal stability is better than that of the traditional Ag-based flexible transparent thin film heater.

[0111] Example 3

[0112] A Ag-based flexible transparent thin film heater with high thermal stability is prepared according to the method of Example 1, except that when preparing the Ga-Ag alloy target, 0.8 mL of liquid Ga is measured with a pipette and dripped onto the A circular Ag sheet with a thickness of 0.1 mm was prepared on the surface of a Ga-Ag target target, and a Ga-Ag alloy target was obtained under the same preparation conditions as in Example 1. The Ga-Ag target target was fixed on the surface of the Ag target so that the target material was completely covered. The atomic content of the Ga-Ag seed layer obtained subsequently was Ga:Ag=13.8:1.

[0113] The Ag film in the Ag-based flexible transparent thin film heater obtained in this embodiment is relatively continuous and has low surface roughness.

[0114] The Ag-based flexible transparent film heater obtained in this embodiment has a high transmittance in the visible light region, up to 90%, and has a 12.9Ω·sq -1 Surface resistance ( Figure 4 ).

[0115] The Ag-based flexible transparent thin film heater obtained in this embodiment was subjected to the same thermal performance test method as in Example 1. The results show that the device can generate a higher heat output and has a faster thermal response speed; the device still has a relatively stable heat output after repeated bending, indicating that the electrode has good compatibility with the flexible substrate; the device can work normally for a long time at an initial heating temperature of 525K, and the temperature drop is small, and the thermal stability is better than that of the traditional Ag-based flexible transparent thin film heater.

[0116] Comparative Example 1

[0117] A Ag-based flexible transparent thin film heater with high thermal stability is prepared according to the method of Example 1, except that a pure Ag target is used instead of a Ga-Ag alloy target, and the atomic content of the subsequently prepared Ga-Ag seed layer is Ga:Ag=0:1.

[0118] The Ag thin film in the Ag-based flexible transparent thin film heater obtained in this embodiment has poor continuity, many holes, and high surface roughness.

[0119] The Ag-based flexible transparent film heater obtained in this embodiment has a low transmittance in the visible light region, with a maximum transmittance of only 86%, and a 12.5Ω·sq -1 Surface resistance ( Figure 4 ).

[0120] The Ag-based flexible transparent thin film heater obtained in this embodiment was subjected to the same thermal performance test method as in Example 1. The results show that the device can generate low heat output and has a slow thermal response speed; the device fails quickly after repeated bending, indicating that the electrode has poor compatibility with the flexible substrate. This device can only work normally for a short time at the initial heating temperature of 525K, and the temperature drops significantly, and the thermal stability is poor ( Figure 7 ).

[0121] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An Ag-based transparent composite electrode, characterized in that: Including SiO arranged from bottom to top x Thin film layer, Ga-Ag seed layer, Ag thin film layer and oxide layer; The atomic content of the Ga-Ag seed layer is Ga:Ag=0.1~14:1; The Ag-based transparent composite electrode is compatible with both hard substrates and flexible substrates; The SiO x The thickness of the film layer is 8~12 nm; The thickness of the Ga-Ag seed layer is less than 2 nm and not 0; The thickness of the Ag thin film layer is 7-8 nm; The oxide layer is 30-40 nm.

2. The Ag-based transparent composite electrode according to claim 1, characterized in that: The SiO x The thickness of the film layer is 10 nm.

3. The Ag-based transparent composite electrode according to claim 1, characterized in that: The thickness of the Ga—Ag seed layer is 1.5 nm.

4. The Ag-based transparent composite electrode according to claim 1, characterized in that: The thickness of the Ag thin film layer is 7.5 nm.

5. The Ag-based transparent composite electrode according to claim 1, characterized in that: The oxide layer is 35 nm.

6. The Ag-based transparent composite electrode according to claim 1, characterized in that: The atomic content of the Ga-Ag seed layer is Ga:Ag=0.9~13.8:1; The oxide is zinc oxide.

7. The Ag-based transparent composite electrode according to claim 1, characterized in that: The atomic content of the Ga-Ag seed layer is 2.8:

1.

8. A method for preparing the Ag-based transparent composite electrode according to any one of claims 1 to 7, characterized in that: The steps include: SiO was deposited on the substrate by magnetron sputtering. x Thin film, substrate / SiO x ; The substrate / SiO x The substrate was used as the substrate, and a Ga-Ag alloy target was used to deposit and grow a Ga-Ag seed layer on it by magnetron sputtering to obtain a substrate / SiO x / Ga-Ag; The substrate / SiO x / Ga-Ag is used as the substrate, and Ag thin film is deposited and grown on it using Ag target by magnetron sputtering to obtain substrate / SiO x / Ga-Ag / Ag; The substrate / SiO x / Ga-Ag / Ag is used as a substrate, and a magnetron sputtering method is used to deposit and grow an oxide film as a protective layer thereon to obtain an Ag-based transparent composite electrode.

9. The method for preparing the Ag-based transparent composite electrode according to claim 8, characterized in that: The substrate is a hard transparent substrate or a flexible transparent substrate; Alternatively, magnetron sputtering under RF power is used to deposit the x / Ga-Ag / Ag substrates, and the oxide was deposited on the substrate / SiO by magnetron sputtering under a DC power supply. x or substrate / SiO x / Metal deposition on Ga-Ag substrate.

10. The method for preparing the Ag-based transparent composite electrode according to claim 9, characterized in that: The substrate is a polyimide film.

11. The method for preparing the Ag-based transparent composite electrode according to claim 9, characterized in that: The purity of all oxide targets used in RF power supplies is ≥99.99%, and the purity of all pure metal targets used in DC power supplies is ≥99.9999%.

12. The method for preparing the Ag-based transparent composite electrode according to claim 8, characterized in that: The preparation method of the Ga-Ag alloy target comprises the following steps: Drop liquid Ga onto the surface of the Ag sheet, then heat the Ag sheet to 30-60°C, evenly apply the liquid Ga to completely cover the surface of the Ag sheet, and keep the temperature constant until Ga corrodes the Ag sheet; After the heat preservation is completed, the Ag thin sheet with Ga on the surface is frozen to obtain a Ga-Ag alloy sheet; According to the requirement of atomic content in the Ga-Ag seed layer, a Ga-Ag alloy sheet is fixed on the surface of the target material at the Ag target position to obtain a Ga-Ag alloy target.

13. The method for preparing the Ag-based transparent composite electrode according to claim 12, characterized in that: The insulation time is 1 to 5 minutes; Or, the freezing time is greater than 2 h.

14. The method for preparing a Ag-based transparent composite electrode according to claim 8, wherein the magnetron sputtering is performed in a vacuum chamber at a temperature of 20-25°C, a distance between the target and the substrate of 18-22 cm, a sputtering angle of 90°, and a base pressure of 3.5×10 -4 Pa, argon is introduced as the protective gas and ionization gas, the gas flow rate is 45~55 sccm, and finally the working gas pressure is maintained at 0.7~1.0 Pa.

15. Use of the Ag-based transparent composite electrode according to any one of claims 1 to 7 in a heater.

16. A Ag-based transparent thin film heater with high thermal stability, characterized in that: It comprises the Ag-based transparent composite electrode as described in any one of claims 1 to 7 and a power source; the Ag-based transparent composite electrode is connected to the power source to form a closed loop.

17. An Ag-based transparent thin film heater with high thermal stability as claimed in claim 16, characterized in that: The power supply is a direct current power supply.

Citation Information

Patent Citations

  • Transparent conductive film of metal silver / metal oxide and preparation method thereof

    CN101697288A

  • Liquid metal target and method for preparing alloy film through liquid metal target

    CN109763109A

  • Ag ALLOY FILM, MANUFACTURING METHOD OF Ag ALLOY FILM, AND Ag ALLOY SPUTTERING TARGET

    JP2017088984A